2001
DOI: 10.1038/oby.2001.3
|View full text |Cite
|
Sign up to set email alerts
|

Is Body Mass Index a Measure of Adiposity in Elderly Women?

Abstract: Research Methods and Procedures:A total of 1423 women aged 67 Ϯ 5 (mean Ϯ SD, range: 60 to 88) years were consecutively enrolled into the study. Fat mass (FM) was measured using DXA. Results: BMI explained 72.9% of FM variance (p Ͻ 0.0001), with a root mean square error of estimate (RMSE) of 3.5 kg. After standardization of RMSE on the dependent variable as RMSE%, the prediction error equaled 15%. BMI explained 54.8% of FM% variance (p Ͻ 0.0001), with an RMSE of 4.1%, corresponding to an RMSE% of 11%. Discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
13

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 13 publications
(16 reference statements)
4
36
2
13
Order By: Relevance
“…In a recent publication on the relationship between excess weight and risk for chronic renal failure showed that the risk of renal failure is three times higher for obese patients [29]. This finding supports the importance of the relationship of obesity to postoperative renal failure found in the sample studied.…”
Section: Discussionsupporting
confidence: 79%
“…In a recent publication on the relationship between excess weight and risk for chronic renal failure showed that the risk of renal failure is three times higher for obese patients [29]. This finding supports the importance of the relationship of obesity to postoperative renal failure found in the sample studied.…”
Section: Discussionsupporting
confidence: 79%
“…BMI and body mass values increase with age, while stature and lean mass decrease. 1,11 However, our findings show that BMI maintained a similar correlation with measures of adiposity in all age groups, which indicates that the relationship between BMI and adiposity remains similar, regardless of ageing. On the other hand, the correlation with tricipital skinfold among men decreased markedly between the middle-aged (40-59.9 years) and elderly groups, and, consequently, so did the correlation with arm fat area.…”
Section: Discussionmentioning
confidence: 35%
“…1 Moreover, the centralization of body fat seems to be a better predictor for complications in this group. 14 Changes related to gains in visceral or subcutaneous fat associated with ageing may be affected by both the initial amount of fat and by increases in body mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…difference between body mass (FM þ FFM) measured by DXA and body weight measured by ADP was À0.8 (0.2) kg (Po0.0001). This difference is low and unlikely to be of practical relevance (Bedogni et al, 2001).…”
Section: Resultsmentioning
confidence: 88%